Primary aldosteronism caused by a pI157S somatic KCNJ5 mutation in a black adolescent female with aldosterone-producing adenoma - Gomez-Sanchez, Celso E.; van Rooyen, Desmaré; Rainey, William E.; Nanba, Kazutaka; Blinder, Amy R.; Baliga, Radhakrishna (Frontiers in Endocrinology, 2022)
Aldosterone-producing adenoma is a rare cause of hypertension in children. Only a limited number of cases of aldosterone-producing adenomas with somatic KCNJ5 gene mutations have been described in children. Blacks are particularly more susceptible to developing long-standing cardiovascular effects of aldosterone-induced severe hypertension. Somatic CACNA1D gene mutations are particularly more prevalent in black males whereas KCNJ5 gene mutations are most frequently present in black females. We present here a novel somatic KCNJ5 p.I157S mutation in an aldosterone-producing adenoma from a 16-year-old black female whose severe drug-resistant hypertension significantly improved following unilateral adrenalectomy. Prompt diagnosis of aldosterone-producing adenoma and early identification of gene mutation would enable appropriate therapy and significantly reduce cardiovascular sequelae.